Recognising the intricate relationship between uric acid and diabetes and its impact on ocular diseases - Soumya Ramani; Smriti Harish (Journal of Clinical Ophthalmology and Research)
A 73-year-old elderly male with uncontrolled diabetes mellitus and hypertension, presented to the outpatient department with a diminution of vision in both eyes for 3 months. He also gave a history of a nonhealing foot ulcer, hyperuricemia, and elevated serum creatinine. After examination, a provisional diagnosis of crystalline maculopathy associated with hyperuricemia was made.